HUBUNGAN KADAR HEMOGLOBIN PADA IBU HAMIL TRIMESTER III DENGAN BERAT BADAN LAHIR BAYI DI TPMB LIDIATI DI DESA PULO KECAMATAN TEMPEH KABUPATEN LUMAJANG - Listiawati, Anni; Maulina, Rifzul; Purwati, Anik (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
Anemic pregmant women has risk of getting a baby with low birth weight and still more common in Indonesia, one of them is the working area of TPMB Lidiati of Pulo empeh Lumajang. This research was conducted to determine the relationship of hemoglobin levels on third trimester pregnant with birth weight infants. The purpose of this study is to identify the relationship of hemoglobin levels in third trimester pregnant with birth weight infants. This study was using cross sectional design that is data acquiring on maternal hemoglobin levels at third trimester and infant birth weight through medical record with once retrieval data. Januari 2023 – Desember 2023 and samples that are used as much as 79 of pregnant women by purposive sampling with only a hemoglobin level of pregnant women during third trimester and birth weight infant born are recorded in medical records. Data analyzing used is a frequency distribution, mean, and Pearson Product Moment. Average of hemoglobin levels on third trimester pregnant was still within the normal range with the prevalence of anemia of 21,5% (higher than government targets) and the average of birth weight by 12,7% (higher than government targets), and with α = 0,05 obtained p-value = 0,0005 dan r-value = +0,870, conclude there is a relationship of hemoglobin levels in third trimester pregnant with birth weight infant with very strong degree of relationship, while high levels of hemoglobin in the third trimester pregnant women, the birth weight infants will hingher.